A reverse travelling wave differential protection scheme for DC lines in MMC–HVDC system with metallic return. (February 2022) - Xue, Shimin; Lu, Junchi; Sun, Yabing; Wang, Shouxiang; Li, Botong; Li, Bin
Abstract: With the increase of voltage level and transmission capacity, the symmetric bipolar modular multilevel converter based high voltage direct current (MMC–HVDC) grid has become popular in actual projects. Due to the DC fault must be cleared within the timeframe of milliseconds, fast and reliable identification of faulty line is a key issue. The grounding method of HVDC grid and the frequency dependent characteristics of transmission line influence the fault characteristics are rarely taken consideration. To make up for the insufficiency, a reverse travelling wave differential protection scheme is proposed in this paper. Based on the grounding mode of metallic return, the compound sequence boundary conditions under different DC faults are derived first. Then, the travelling wave theory based on Marti frequency dependent model is analysed, and the reverse travelling wave differential value is calculated. Based on the analysis, the protection strategy of different DC faults is established. The proposed protection scheme can meet the rapidity requirements, with low sampling frequency and easy setting. The effectiveness is verified by PSCAD/EMTDC, and extensive simulation results are carried out to verify the advantages in fault resistance tolerance and anti-interference capability. Highlights: The grounding method of metallic return leads to the fault type more complicated. The compound sequence boundary conditions under different DC faults are derived. The frequency dependent parameter line model provides more fault information. The reverse travelling wave differential values are adopted. Extensive simulation results prove the advantages of the proposed protection.